Preparation method of solid spherical silicon dioxide micro powder
By reacting in a water-in-oil microemulsion to generate silica acid and polymerize and hydrolyze, the problems of low strength and easy powdering of spherical silica powder were solved, and solid spherical silica with high spherical shape and uniform particle size distribution were prepared. Micropowder meets the application needs of high-performance materials.
Patent Information
- Application Number
- CN202411622549.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, when preparing spherical silica fine powder, powder agglomeration occurs, resulting in low strength and easy powdering, which cannot meet the needs of use in infrared invisibility, polishing abrasives, toothpaste filling materials and other fields.
In a water-in-oil microemulsion composed of mineral oil and surfactant, silicate acid is formed by reacting sodium silicate solution with sulfuric acid, polymerizing and hydrolyzing, forming solid spherical silica fine powder with good dispersion and high spherical shape.
The prepared solid spherical silica micropowder has a smooth surface and no agglomeration. It has a spherical degree of up to 1, a uniform particle size distribution, an average particle size greater than 70μm and a specific surface area less than 7m2/g, meeting the needs of high-performance materials.
Smart Images

Figure CN119390078A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon dioxide micropowder preparation, and in particular to a method for preparing solid spherical silicon dioxide micropowder. Background Art
[0002] Silica powder is an odorless, non-toxic, non-polluting inorganic non-metallic material. Spherical silica powder has excellent properties such as high light transmittance, high dielectric constant, high moisture resistance, high filling volume, low expansion, low stress and low friction coefficient. It is widely used in many fields such as large-scale integrated circuit packaging, aerospace, catalysts, adhesives, coatings, medicine and daily cosmetics. It is an irreplaceable important material.
[0003] The preparation methods of spherical silica powder mainly include physical method and chemical method. The physical method includes flame spheroidization, high temperature melt spraying, self-propagating low temperature combustion, plasma method and high temperature calcination spheroidization, etc. The chemical method includes gas phase method, hydrothermal synthesis method, sol-gel method, precipitation method, microemulsion method, etc. The sol-gel method mainly produces silica particles by hydrolyzing ethyl orthosilicate. The obtained product has defects such as micropores, looseness, poor density, easy differentiation, and low strength, which is not suitable for the field of electronic packaging. Although the precipitation method has easy-to-obtain raw materials and simple process, the particle size distribution of the spherical silica particles obtained is difficult to control, the spheroidization rate is low, and the agglomeration phenomenon is serious. The microemulsion method is to use two immiscible inorganic phases and organic phases to form a uniform emulsion under the action of a surfactant, so that the processes such as nucleation, growth, aggregation, and agglomeration are confined to a tiny spherical droplet, and then the solid phase is precipitated from the emulsion to form spherical particles. In contrast, the spherical silica powder prepared by the microemulsion method has better comprehensive performance and is the most widely used. For example, Chinese patent CN102795630A discloses the preparation of silica by the reverse microemulsion method, and silicon tetrachloride is added to the compounded reverse microemulsion system for reaction, demulsification, drying and other steps to obtain micron or nanometer-level monodispersed silica powder. Chinese patent CN112194142A discloses a method for preparing high-purity spherical silica, adding chlorosilane to a microemulsion system containing alcohol substances for alcoholysis and hydrolysis to obtain silica; the prepared silica has high purity, high sphericity, small particle size, good dispersibility, and stable reaction and is easy to control. Chinese patent CN113968584A discloses that industrial water glass is used as a silicon source, and spherical micelles constructed with surfactants and inorganic metal salts adsorb metal ions to form a spherical shell of a metal silicate, and a spherical shell of silicon dioxide is generated under the action of an acidifier, and impurities are removed by washing and burning to obtain hollow spherical silicon dioxide. Chinese patent CN115784245A discloses a method for preparing hydrophobic high-purity micron-level spherical silicon dioxide powder, which obtains a silicic acid solution of an aqueous phase after removing metal impurities with a strong acid cation exchange resin, and then mechanically emulsifies and heats after mixing with an oil phase, a surfactant and a co-surfactant, and then solidifies, separates, washes and dries after surface hydrophobic treatment with an organic silane, and obtains a spherical silicon dioxide powder by adding an alkaline precipitant. European patent WO2023178210A1 discloses that sodium silicate reacts with acid to generate silica sol, and then performs oil-in-water emulsification under the action of surfactant to prepare porous material spherical silica with a particle size of less than 50 μm and a pore volume of more than 1.0 cm 3 / g, specific surface area greater than 400m 2 / g, used as catalytic carrier.
[0004] At present, silica micropowder with high spheroidization rate can be prepared through oil-in-water microemulsion system, but there is still serious powder agglomeration phenomenon, resulting in spherical silica micropowder with high specific surface area and pore structure, low strength and easy pulverization, which cannot meet the use requirements in the fields of infrared stealth, polishing abrasives, toothpaste filling materials, etc. Therefore, the preparation of solid silica micropowder with large particle size, high dispersibility, high sphericity and controllable particle size distribution has broad application value. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing solid spherical silicon dioxide powder in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing solid spherical silicon dioxide powder, comprising the following steps:
[0008] (1) mixing a sodium silicate solution, mineral oil and a surfactant and stirring to obtain a water-in-oil emulsion;
[0009] (2) adding sulfuric acid dropwise to the water-in-oil emulsion for aging to obtain a polymerized silicate emulsion;
[0010] (3) gelling the polymerized silicate emulsion to obtain a polymerized gel;
[0011] (4) mixing the demulsifier and the polymer gel, performing demulsification treatment in sequence, and standing to obtain an aqueous phase;
[0012] (5) The aqueous phase is dried and calcined in sequence to obtain solid spherical silica powder.
[0013] Preferably, in step (1), the mass ratio of the sodium silicate solution, mineral oil and surfactant is 1:0.5-3:0.03-0.15, the mass concentration of the sodium silicate solution is 5-40%, and the temperature of the sodium silicate solution is 5-35°C.
[0014] Preferably, the mineral oil in step (1) comprises one or more of paraffin oil, heavy lamp oil and heavy kerosene;
[0015] The surfactant comprises one or more of polyethylene glycol monolaurate, glycerol monolaurate, N,N-dimethylhexanamide, polyglycerol fatty acid ester, polyethylene glycol dilaurate, lauric acid diglyceride, sorbitol monolaurate and nonylphenoxypolyethoxyethanol.
[0016] Preferably, the stirring speed in step (1) is 500 to 4000 rpm, and the stirring time is 0.5 to 30 min.
[0017] Preferably, the mass concentration of the sulfuric acid in step (2) is 10-65%, the temperature of the sulfuric acid is 5-35° C., the mass ratio of sulfuric acid to the sodium silicate solution in step (1) is 0.05-0.1:1, and the dropping time is 0.1-2 h.
[0018] Preferably, the aging temperature in step (2) is 30 to 80° C., and the aging time is 0.5 to 2 h.
[0019] Preferably, the temperature of the gelation treatment in step (3) is 30-100° C., the time of the gelation treatment is 0.5-10 h, and the pH value of the gelation treatment is 1.5-5.5.
[0020] Preferably, the demulsifier in step (4) is sulfuric acid, and the mass concentration of the sulfuric acid is 5-30%; the mass ratio of the demulsifier to the sodium silicate solution in step (1) is 0.3-0.8:1.
[0021] Preferably, the temperature of the demulsification treatment in step (4) is 30-80° C., the time of the demulsification treatment is 0.25-3 h, and the standing time is 0.25-3 h.
[0022] Preferably, the drying temperature in step (5) is 80-120° C., and the drying time is 20-28 h; the roasting temperature is 250-900° C., and the roasting time is 2-12 h.
[0023] Beneficial effects of the present invention:
[0024] In the present invention, in the environment of an oil-in-water microemulsion composed of mineral oil and a surfactant, a sodium silicate solution reacts with sulfuric acid to generate silicic acid, which is polymerized into a fine spherical silica sol, and further hydrolyzed to generate a high-value-added solid spherical silica micropowder with good dispersibility and high sphericity. The preparation method of the present invention avoids generating silica sol first, but generates silica by adding sulfuric acid first, and generates silica sol through aging, colloid growth, and gelation, and further demulsifies to obtain solid spherical silica micropowder; the preparation method is simple, the raw materials are cheap and easy to obtain, there is no environmental pollution, and it is easy to industrialize. The solid spherical silica micropowder prepared by the present invention has a smooth surface, no agglomeration, a sphericity of up to 1, a uniform particle size distribution, an average particle size greater than 70μm, and a specific surface area of less than 7m 2 / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of the solid spherical silica powder prepared in Example 1. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing solid spherical silicon dioxide powder, comprising the following steps:
[0027] (1) mixing a sodium silicate solution, mineral oil and a surfactant and stirring to obtain a water-in-oil emulsion;
[0028] (2) adding sulfuric acid dropwise to the water-in-oil emulsion for aging to obtain a polymerized silicate emulsion;
[0029] (3) gelling the polymerized silicate emulsion to obtain a polymerized gel;
[0030] (4) mixing the demulsifier and the polymer gel, performing demulsification treatment in sequence, and standing to obtain an aqueous phase;
[0031] (5) The aqueous phase is dried and calcined in sequence to obtain solid spherical silica powder.
[0032] In the present invention, in the environment of a water-in-oil microemulsion composed of a surfactant and mineral oil, a sodium silicate solution reacts with sulfuric acid to generate silicic acid, which is further polymerized and hydrolyzed into a solid spherical silicon dioxide powder with good dispersibility. The reaction formula is:
[0033] ①Silicic acid generation: Na2SiO3+H2SO4→H2SiO3+Na2SO4
[0034] ②Silicic acid polymerization: nH2SiO3→HO-(SiO2)n-H+(n-1)H2O
[0035] In the present invention, the mass ratio of the sodium silicate solution, mineral oil and surfactant in step (1) is preferably 1:0.5-3:0.03-0.15, more preferably 1:1-2.5:0.04-0.1, and more preferably 1:1.2-1.5:0.05-0.07; the mass concentration of the sodium silicate solution is preferably 5-40%, more preferably 7.5-30%, and more preferably 10-25%; the temperature of the sodium silicate solution is preferably 5-35°C, more preferably 10-30°C, and more preferably 15-25°C.
[0036] In the present invention, the mixing in step (1) is preferably performed by first mixing the sodium silicate solution, the surfactant and the first part of the mineral oil to obtain a mixed emulsion; and then mixing the mixed emulsion with the second part of the mineral oil to obtain an oil-in-water emulsion; the mass ratio of the first part of the mineral oil to the second part of the mineral oil is preferably 1.2 to 2.4:1, and more preferably 1.8:1.
[0037] In the present invention, the mineral oil in step (1) preferably comprises one or more of paraffin oil, heavy lamp oil and heavy kerosene;
[0038] The surfactant preferably comprises one or more of polyethylene glycol monolaurate, glycerol monolaurate, N,N-dimethylhexanamide, polyglycerol fatty acid ester, polyethylene glycol dilaurate, diglycerol laurate, sorbitan monolaurate and nonylphenoxypolyethoxyethanol.
[0039] In the present invention, the stirring speed in step (1) is preferably 500 to 4000 rpm, more preferably 1000 to 3000 rpm, and more preferably 2000 rpm; the stirring time is preferably 0.5 to 30 min, more preferably 5 to 20 min, and more preferably 10 to 15 min.
[0040] In the present invention, the mass concentration of the sulfuric acid in step (2) is preferably 10-65%, more preferably 15-50%, and more preferably 20-45%; the temperature of the sulfuric acid is preferably 5-35°C, more preferably 10-30°C, and more preferably 15-25°C; the mass ratio of sulfuric acid to the sodium silicate solution in step (1) is preferably 0.05-0.1:1, more preferably 0.06-0.09:1, and more preferably 0.07-0.08:1; the time for the dropwise addition is preferably 0.1-2h, more preferably 0.5-1.5h, and more preferably 1h.
[0041] In the present invention, the aging temperature in step (2) is preferably 30 to 80° C., more preferably 40 to 70° C., and more preferably 50 to 60° C.; the aging time is preferably 0.5 to 2 h, and more preferably 1 to 1.5 h.
[0042] In the present invention, aging is the process of silicic acid polymerization to generate polysilicic acid colloid particles.
[0043] In the present invention, the temperature of the gelation treatment in step (3) is preferably 30 to 100°C, more preferably 50 to 90°C, and more preferably 60 to 80°C; the time of the gelation treatment is preferably 0.5 to 10 h, more preferably 2 to 8 h, and more preferably 5 to 6 h; the pH value of the gelation treatment is preferably 1.5 to 5.5, more preferably 2.0 to 4.5, and more preferably 3.0 to 4.0.
[0044] In the present invention, the gelation treatment is the process of dehydration and growth of polysilicic acid colloid particles.
[0045] In the present invention, in step (3), a sodium hydroxide solution is preferably used to adjust the pH value of the gelation treatment, and the mass concentration of the sodium hydroxide solution is preferably 20-40%, and more preferably 30%.
[0046] In the present invention, the demulsifier in step (4) is preferably sulfuric acid, and the mass concentration of sulfuric acid is preferably 5-30%, more preferably 10-25%, and more preferably 15-20%; the mass ratio of the demulsifier to the sodium silicate solution in step (1) is preferably 0.3-0.8:1, more preferably 0.4-0.7:1, and more preferably 0.5-0.6:1.
[0047] In the present invention, the temperature of the demulsification treatment in step (4) is preferably 30 to 80°C, more preferably 40 to 70°C, and more preferably 50 to 60°C; the time of the demulsification treatment is preferably 0.25 to 3h, more preferably 0.5 to 2h, and more preferably 1 to 1.5h; the standing time is preferably 0.25 to 3h, more preferably 0.5 to 2h, and more preferably 1 to 1.5h.
[0048] In the present invention, the demulsification treatment in step (4) is preferably carried out under stirring, and the stirring speed is preferably 500 to 4000 rpm, and more preferably 2000 to 3000 rpm.
[0049] In the present invention, the aqueous phase of step (5) is preferably filtered and washed in sequence and then dried and calcined in sequence; the filtration accuracy is preferably 10 to 40 μm, and more preferably 20 to 30 μm; the reagent used for washing is preferably water, and the pH value of the filtrate after washing is preferably 3.0 to 7.0, more preferably 3.5 to 6.0, and more preferably 4.0 to 5.0.
[0050] In the present invention, the drying temperature in step (5) is preferably 80-120°C, more preferably 90-110°C, and more preferably 100°C; the drying time is preferably 20-28h, more preferably 22-26h, and more preferably 24h; the calcination temperature is preferably 250-900°C, more preferably 300-800°C, and more preferably 400-600°C; the calcination time is preferably 2-12h, more preferably 3-10h, and more preferably 5-6h.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 15° C. and the mass concentration is 7.5%) is mixed with 900 g of heavy kerosene and 65 g of polyethylene glycol (200) monolaurate, and stirred at a speed of 2000 rpm for 5 min to obtain a mixed emulsion; the mixed emulsion is then added to 500 g of heavy kerosene, and stirred at a speed of 2000 rpm for 5 min to obtain an oil-in-water emulsion.
[0054] 100 g of sulfuric acid (the temperature of the sulfuric acid is 15° C. and the mass concentration is 65%) was added dropwise to the water-in-oil emulsion for 30 minutes, and then the solution was placed at 50° C. for aging for 1 hour to obtain a polysilicic acid emulsion. The pH value of the polysilicic acid emulsion was adjusted to 3.5 using a sodium hydroxide solution with a mass concentration of 30%, and then placed at 50° C. for gelation for 2 hours to obtain a polymer gel.
[0055] 500g of sulfuric acid (the mass concentration of sulfuric acid is 10%) is mixed with the polymer gel, and stirred at 50°C for 0.5h at a speed of 500rpm for demulsification. The mixed solution after demulsification is allowed to stand for 0.5h for oil-water phase separation to obtain an aqueous phase. The aqueous phase is filtered (the filtration accuracy is 40μm) and washed with deionized water until the pH value of the filtrate is 3.5 to obtain a precursor. The precursor is first dried at 110°C for 24h, and then calcined at 300°C for 6h to obtain solid spherical silica powder.
[0056] Example 2
[0057] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 15° C. and the mass concentration is 7.5%) is mixed with 650 g of heavy kerosene and 65 g of polyethylene glycol (200) monolaurate, and stirred at a speed of 2000 rpm for 5 min to obtain a mixed emulsion; the mixed emulsion is then added to 500 g of heavy kerosene, and stirred at a speed of 2000 rpm for 5 min to obtain an oil-in-water emulsion.
[0058] The rest is the same as in Example 1.
[0059] Example 3
[0060] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 15° C. and the mass concentration is 7.5%) is mixed with 1200 g of heavy kerosene and 65 g of polyethylene glycol (200) monolaurate, and stirred at a speed of 2000 rpm for 5 min to obtain a mixed emulsion; the mixed emulsion is then added to 500 g of heavy kerosene, and stirred at a speed of 2000 rpm for 5 min to obtain an oil-in-water emulsion.
[0061] The rest is the same as in Example 1.
[0062] Example 4
[0063] The mass of polyethylene glycol (200) monolaurate in Example 1 was modified to 50 g, and the rest was the same as in Example 1.
[0064] Example 5
[0065] The mass of polyethylene glycol (200) monolaurate in Example 1 was modified to 80 g, and the rest was the same as in Example 1.
[0066] Example 6
[0067] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 15° C. and the mass concentration is 7.5%) is mixed with 900 g of heavy kerosene and 65 g of polyethylene glycol (200) monolaurate, and stirred at 3000 rpm for 5 min to obtain a mixed emulsion; the mixed emulsion is then added to 500 g of heavy kerosene, and stirred at 3000 rpm for 5 min to obtain an oil-in-water emulsion.
[0068] The rest is the same as in Example 1.
[0069] Example 7
[0070] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 15° C. and the mass concentration is 7.5%) is mixed with 900 g of heavy kerosene and 65 g of polyethylene glycol (200) monolaurate, and stirred at a speed of 2000 rpm for 5 min to obtain a mixed emulsion; the mixed emulsion is then added to 700 g of heavy kerosene, and stirred at a speed of 2000 rpm for 5 min to obtain an oil-in-water emulsion.
[0071] The rest is the same as in Example 1.
[0072] Example 8
[0073] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 5° C. and the mass concentration is 30%) is mixed with 600 g of paraffin oil and 180 g of sorbitan monolaurate, and stirred at 4000 rpm for 15 min to obtain a mixed emulsion; the mixed emulsion is then added to 400 g of paraffin oil, and stirred at 4000 rpm for 10 min to obtain an oil-in-water emulsion.
[0074] 108 g of sulfuric acid (the temperature of the sulfuric acid is 25° C. and the mass concentration is 15%) was added dropwise to the water-in-oil emulsion for 1.5 h, and then the solution was aged at 60° C. for 2 h to obtain a polymerized silicate emulsion. The pH value of the polymerized silicate emulsion was adjusted to 2.0 using a sodium hydroxide solution having a mass concentration of 20%, and then the solution was gelled at 90° C. for 0.5 h to obtain a polymerized gel.
[0075] 840g of sulfuric acid (the mass concentration of sulfuric acid is 20%) is mixed with the polymer gel, and stirred at 70°C for 0.25h at a speed of 4000rpm for demulsification. The mixed solution after demulsification is allowed to stand for 2h for oil-water phase separation to obtain an aqueous phase. The aqueous phase is filtered (the filtration accuracy is 10μm) and washed with deionized water until the pH value of the filtrate is 5.0 to obtain a precursor. The precursor is first dried at 90°C for 26h, and then calcined at 800°C for 3h to obtain solid spherical silica powder.
[0076] Example 9
[0077] 1200 g of sodium silicate solution (the temperature of the sodium silicate solution is 5° C. and the mass concentration is 10%) is mixed with 1900 g of heavy kerosene and 120 g of nonylphenoxypolyethoxyethanol, and stirred at a speed of 500 rpm for 20 min to obtain a mixed emulsion; then the mixed emulsion is added to 1000 g of heavy kerosene, and stirred at a speed of 500 rpm for 10 min to obtain an oil-in-water emulsion.
[0078] 60 g of sulfuric acid (the temperature of sulfuric acid is 10° C. and the mass concentration is 45%) was added dropwise to the water-in-oil emulsion for 60 min, and then the emulsion was aged at 30° C. for 0.5 h to obtain a polysilicic acid emulsion. The pH value of the polysilicic acid emulsion was adjusted to 4.5 using a sodium hydroxide solution with a mass concentration of 40%, and then the emulsion was gelated at 90° C. for 10 h to obtain a polymer gel.
[0079] 600g of sulfuric acid (the mass concentration of sulfuric acid is 5%) is mixed with the polymer gel, and stirred at 30°C for 3h at a speed of 500rpm for demulsification. The mixed solution after demulsification is allowed to stand for 3h for oil-water phase separation to obtain an aqueous phase. The aqueous phase is filtered (the filtration accuracy is 40μm) and washed with deionized water until the pH value of the filtrate is 6.0 to obtain a precursor. The precursor is first dried at 120°C for 20h, and then calcined at 600°C for 10h to obtain solid spherical silica powder.
[0080] The average particle size D of the solid spherical silica powder of Examples 1 to 9 was measured according to GB30451. 50 , particle size Span value, sphericity and specific surface area. The measurement results are shown in Table 1.
[0081] Table 1 Properties of solid spherical silica powder
[0082]
[0083]
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing solid spherical silicon dioxide powder, characterized in that: The following steps are included: (1) mixing a sodium silicate solution, mineral oil and a surfactant and stirring to obtain a water-in-oil emulsion; (2) adding sulfuric acid dropwise to the water-in-oil emulsion for aging to obtain a polymerized silicate emulsion; (3) gelling the polymerized silicate emulsion to obtain a polymerized gel; (4) mixing the demulsifier and the polymer gel, performing demulsification treatment in sequence, and standing to obtain an aqueous phase; (5) The aqueous phase is dried and calcined in sequence to obtain solid spherical silica powder.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the sodium silicate solution, mineral oil and surfactant is 1:0.5-3:0.03-0.15, the mass concentration of the sodium silicate solution is 5-40%, and the temperature of the sodium silicate solution is 5-35°C.
3. The preparation method according to claim 1 or 2, characterized in that: The mineral oil in step (1) comprises one or more of paraffin oil, heavy lamp oil and heavy kerosene; The surfactant comprises one or more of polyethylene glycol monolaurate, glycerol monolaurate, N,N-dimethylhexanamide, polyglycerol fatty acid ester, polyethylene glycol dilaurate, lauric acid diglyceride, sorbitol monolaurate and nonylphenoxypolyethoxyethanol.
4. The preparation method according to claim 3, characterized in that: The stirring speed in step (1) is 500 to 4000 rpm, and the stirring time is 0.5 to 30 min.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the sulfuric acid in step (2) is 10-65%, the temperature of the sulfuric acid is 5-35° C., the mass ratio of sulfuric acid to the sodium silicate solution in step (1) is 0.05-0.1:1, and the dripping time is 0.1-2h.
6. The preparation method according to claim 4 or 5, characterized in that: The aging temperature in step (2) is 30 to 80° C., and the aging time is 0.5 to 2 hours.
7. The preparation method according to claim 6, characterized in that: The temperature of the gelation treatment in step (3) is 30-100° C., the time of the gelation treatment is 0.5-10 h, and the pH value of the gelation treatment is 1.5-5.
5.
8. The preparation method according to claim 7, characterized in that: The demulsifier in step (4) is sulfuric acid, and the mass concentration of the sulfuric acid is 5-30%; the mass ratio of the demulsifier to the sodium silicate solution in step (1) is 0.3-0.8:
1.
9. The preparation method according to claim 7 or 8, characterized in that: The temperature of the demulsification treatment in step (4) is 30 to 80° C., the time of the demulsification treatment is 0.25 to 3 hours, and the standing time is 0.25 to 3 hours.
10. The preparation method according to claim 9, characterized in that: In step (5), the drying temperature is 80-120° C. and the drying time is 20-28 hours; the roasting temperature is 250-900° C. and the roasting time is 2-12 hours.
Citation Information
Patent Citations
Method for preparing silicon dioxide by using reverse micro-emulsion method
CN102795630A
Method for preparing high-purity spherical silicon dioxide and high-purity spherical silicon dioxide
CN112194142A
Hollow spherical silicon dioxide and preparation method thereof
CN113968584A
Preparation method of hydrophobic high-purity micron-sized spherical silicon dioxide powder
CN115784245A
Process for producing porous spherical silica GEL particles
WO2023178210A1